Value of exercise echocardiography in heart failure with preserved ejection fraction: a substudy from the KaRen study. (16th June 2015) - Donal, Erwan; Lund, Lars H.; Oger, Emmanuel; Reynaud, Amélie; Schnell, Frédéric; Persson, Hans; Drouet, Elodie; Linde, Cecilia; Daubert, Claude
Abstract: Background: KaRen is a multicentre study designed to characterize and follow patients with heart failure and preserved ejection fraction (HFpEF). In a subgroup of patients with clinical signs of congestion but left ventricular ejection fraction (LVEF) >45%, we sought to describe and analyse the potential prognostic value of echocardiographic parameters recorded not only at rest but also during a submaximal exercise stress echocardiography. Exercise-induced changes in echo parameters might improve our ability to characterize HFpEF patients. Method and results: Patients were prospectively recruited in a single tertiary centre following an acute HF episode with NT-pro-BNP >300 pg/mL (BNP > 100 pg/mL) and LVEF > 45% and reassessed by exercise echo-Doppler after 4–8 weeks of dedicated treatment. Image acquisitions were standardized, and analysis made at end of follow-up blinded to patients' clinical status and outcome. In total, 60 patients having standardized echocardiographic acquisitions were included in the analysis. Twenty-six patients (43%) died or were hospitalized for HF (primary outcome). The mean ± SD workload was 45 ± 14 watts (W). Mean ± SD resting LVEF and LV global longitudinal strain was 57.6 ± 9.5% and −14.5 ± 4.2%, respectively. Mean ± SD resting E / e ′ was 11.3 ± 4.7 and 13.1 ± 5.3 in those patients who did not and those who did experience the primary outcome, respectively ( P = 0.03). Tricuspid regurgitation (TR) peak velocity during exercise were 3.3 ± 0.5 and 3.7 ± 0.5 m/s ( P = 0.01). Exercise TR was independently associated with HF-hospitalization or death after adjustment on baseline clinical and biological characteristics. Conclusion: Exercise echocardiography may contribute to identify HFpEF patients and especially high-risk ones. Our study suggested a prognostic value of TR recorded during an exercise. That was demonstrated independently of the value of resting E / e ′.